Cover, Editorial Board, Foreword, Table of Content: Metaphor Vol. 4 No. 1 September 2021 - Latifah Dwi Ariyani (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2021)
Cover, Editorial Board, Foreword, Table of Content: Metaphor Vol. 4 No. 1 September 2021